A THEORETICAL APPROACH TO THE TOURISM BUSINESSES MARKETING PLAN AND MANAGEMENT PROCESS (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The aim of this study was to identify the importance of marketing plan and management practices at tourism businesses. To perform of this aim, the literature was searched and some related studies which  published at the marketing area were used. According to the results of the study, it was found that marketing plan and its management process is an important factor increasing both sales and profit rates at tourism busienesses.